STRUKTUR KEPEMILIKAN, PROFITABILITAS, DAN RISIKO PERUSAHAAN TERHADAP STRUKTUR MODAL DAN NILAI PERUSAHAAN - Kellen, Pius Bumi (University of Merdeka Malang, 2011)
This study aimed to examine and analyze the effect of ownership structure, corporate growth, corporateprofitability and risk of capital structure as well as the influence of four determinants and capital structure onfirm value. Originality of this study was the addition of risk variables with indicator accounting firm beta. Thestudy used panel data namely merging cross-section (36 companies) and time series data (5 years) sourcedfrom secondary data analysis with 180 units. Analysis of data used a model of Partial Least Square (PLS). Thestudy found that ownership structure did not have significant negative effect on capital structure and significantimpact on corporate value. The company growth did not have significant negative effect on capitalstructure and corporate value. Profitability did not have significant positive effect on capital structure and ithad significant impact on corporate value. Corporate risk had a positive effect, no significant effect on capitalstructure and corporate value, capital structure and it had a significant negative effect on firm value.